2019
DOI: 10.21608/ajnsa.2019.12389.1212
|View full text |Cite
|
Sign up to set email alerts
|

Uranium Partitioning During Water Treatment Processes

Abstract: Some of non-renewable water resources such as deep groundwater aquifers were explored extensively for the use as drinking water. Water treatment plants (WTPs) were established to fulfill the standards of drinking water quality. The study of the chemical behavior of uranium (U) in groundwater treatment process is the main aim of this work that will shed more light on U removal efficiency during water treatment processes. Samples represent various treatment processes such as sand filtration and reverse osmosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Due to dissolution Zn may release from that molecule and U could bonded with sulphate [20]. It can explain the U correlation with SO 4 (0.70 p<0.5) which can be from agricultural or geological sources from the youngest sediment layers [8,44,45]. This is similar to some studies where high U concentrations in groundwater were found from quaternary and tertiary sediments regions that exhibited U detectable concentrations meanwhile in paozoic and Jurassic rock sediments show low detectable concentration [46].…”
Section: Elemental Correlationsmentioning
confidence: 99%
“…Due to dissolution Zn may release from that molecule and U could bonded with sulphate [20]. It can explain the U correlation with SO 4 (0.70 p<0.5) which can be from agricultural or geological sources from the youngest sediment layers [8,44,45]. This is similar to some studies where high U concentrations in groundwater were found from quaternary and tertiary sediments regions that exhibited U detectable concentrations meanwhile in paozoic and Jurassic rock sediments show low detectable concentration [46].…”
Section: Elemental Correlationsmentioning
confidence: 99%
“…The existence of 238 U in aquifer rock, CO 2 , dynamic agents, and oxygen in the aquifer all affect the value of 238 U in water. Temperature, pH, flow rate, value and characteristics of dissolved salts, and residence time are all characteristics of water that can be used to estimate its capacity to dissolve, hold, or deposit elements (Khater et al, 2008). 238 U enters the human body mostly by consuming groundwater , breathing air, or eating food, with 85% of uranium entering through water and 15% through food (Santos Amaral et al, 2005).…”
Section: Introductonmentioning
confidence: 99%